Chemistry of group 9 dimetallaborane analogues of octaborane(12). Issue 2 (11th November 2014) - Barik, Subrat Kumar; Roy, Dipak Kumar; Ghosh, Sundargopal
Abstract : Reaction of octaborane(12) analogue with metal carbonyl compounds yielded condensed metallaborane (A) and boride cluster (B). Abstract : We report the synthesis, isolation and structural characterization of several moderately air stable nido -metallaboranes that represent boron rich open cage systems. The reaction of [Cp*CoCl]2, (Cp* = η 5 -C5 Me5 ), with [BH3 ·thf] in toluene at ice cold temperature, followed by thermolysis in boiling toluene produced [(Cp*Co)B9 H13 ], 1 [(Cp*Co)2 B8 H12 ], 2 and [(Cp*Co)2 B6 H10 ]3 . Building upon our earlier reactivity studies on rhodaboranes, we continue to explore the reactivity of dicobalt analogues of octaborane(12) cluster3 with [Fe2 (CO)9 ] and [Ru3 (CO)12 ] at ambient conditions that yielded novel fused clusters [Fe2 (CO)6 (Cp*Co)2 B6 H10 ], 4 and [Ru4 (CO)11 (Cp*Co)2 B3 H3 ], 5 respectively. In an attempt to synthesize a heterometallic metallaborane compound we performed the reaction of [(Cp*Rh)2 B6 H10 ], 6 with [Cp*IrH4 ] that yielded a Ir–Ir double bonded compound [(Cp*Ir)2 H3 ][B(OH)4 ], 7 . All the new compounds have been characterized by IR, 1 H, 11 B, 13 C NMR spectroscopy, and the molecular structures were unambiguously established by X-ray diffraction analysis.